Analysis of sexism and feminism in the future teaching profession - Fernández Rotaeche, Patricia; Jauregizar Albóniga-Mayor, Joana; Idoiaga Mondragón, Nahia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study aims to analyse sexism and feminism in prospective teachers. The sample is composed of 692 people and the data were obtained by administering the ISA scale to measure ambivalent sexism (hostile and benevolent) and the self-identification as feminist scale to measure feminist identification. The results show that men have higher levels of both hostile and benevolent sexism than women, and that women identify more with feminism. We also find that the higher the level of education, the lower the sexist attitudes. In conclusion, it seems that education is a good tool to work on both sexism and feminism.